Aspergillus DNA contamination in blood collection tubes - Harrison, Elizabeth (2010)
Fungal PCR-based diagnostic methods are at risk of contamination. Sample collection containers were investigated for fungal DNA contamination using real-time PCR assays. Up to 18% of blood collection tubes were contaminated with fungal DNA, probably A. fumigatus. Lower proportions of contamination in other vessels were observed.